3d-printed green concrete material, mortar, component and method of production

By using high-solid-waste, low-alkali cementitious materials, low-pH sulfoaluminate cement clinker, and fluorogypsum, combined with spherical ceramic sand and sand particles, a vegetated concrete material suitable for 3D printing was prepared. This solved the compatibility problem between 3D printing and vegetated concrete, and enabled concrete components with high porosity and low alkalinity, which are suitable for plant growth and efficient design.

CN118184277BActive Publication Date: 2026-11-06ZHEJIANG JIZHU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410262420.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-07
Publication Date
2026-11-06
Estimated Expiration
2044-03-07

AI Technical Summary

Technical Problem

Existing technologies cannot simultaneously meet the requirements of 3D printed concrete and planted concrete, especially the requirements of high porosity and low alkalinity, resulting in unsuitable plant growth and limited component design.

Method used

By using high-solid-waste, low-alkali cementitious materials, combined with low-pH sulfoaluminate cement clinker and fluorogypsum, along with spherical ceramic sand and sand particles, a 3D-printed vegetated concrete material with fluidity, extrudability, crack resistance, high porosity, and low alkalinity was prepared.

Benefits of technology

This approach achieves a suitable growth environment for planted concrete and efficient component design through 3D printing, improving the porosity and strength of concrete components to meet the needs of plant growth, while also reducing alkalinity and improving construction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004731300700000181
    Figure BDA0004731300700000181
  • Figure BDA0004731300700000182
    Figure BDA0004731300700000182
Patent Text Reader

Abstract

The application provides a 3D printing greening concrete material, mortar, component and a preparation method, and relates to the field of greening concrete. The 3D printing greening concrete material comprises, in terms of weight parts, high solid waste low alkali cementing material 100 parts, sand particles 60-70 parts, spherical ceramic sand 10-35 parts, a retarder 0.10-0.30 parts, a hardening accelerator 0.02-0.04 parts, a water-retaining agent 0.03-0.05 parts, a thixotropic lubricant 0.30-0.60 parts and water 35-45 parts. In the 3D printing greening concrete material, the high solid waste low alkali cementing material is used to replace ordinary Portland cement, and low-pH-value sulphoaluminate cement clinker and fluorogypsum are used, so that the alkalinity of the system can be effectively reduced, and the strength of the concrete component can be ensured. The concrete material has the properties of fluidity, extrudability, buildability, anti-cracking performance, macroporosity and low alkalinity, and meets the requirements of greening concrete and 3D printing concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of vegetation concrete, and more particularly to 3D printed vegetation concrete materials, mortars, components, and preparation methods. Background Technology

[0002] Vegetated concrete is a type of concrete with a continuous macroporous structure, allowing for the growth of green plants on its surface. Researching and applying vegetated porous concrete to urban landscape surfaces, road slope protection, and greening is of great significance. On the one hand, it achieves ground hardening or slope reinforcement; on the other hand, it allows the growth of grasses and other plants, achieving greening and soil and water conservation. There are three key challenges in realizing the functional uses of vegetated concrete: ① Conventional concrete is relatively dense internally, with few pores and impermeability, which is not conducive to soil and nutrient retention and plant root growth; ② The silicate cement used in ordinary concrete produces a large amount of Ca(OH)2 after hydration, resulting in a highly alkaline environment with a pH value greater than 12, which is detrimental to plant growth; ③ Personalized vegetated concrete designs face technical difficulties in preparation. The commonly used prefabrication method for vegetated concrete aims to reduce formwork costs, but the number of molds produced is limited, resulting in a limited variety of specifications and shapes for the produced vegetated concrete components, making it difficult to achieve personalized design and customized supply. To address the above issues, many scholars have proposed corresponding technical solutions, such as using single-graded aggregates instead of continuously graded aggregates to improve the porosity of planted concrete; alkali reduction measures mainly include adding mineral admixtures and acidic additives to concrete, selecting neutral cementitious materials, surface treatment, and carbonation to reduce alkali; and using customized molds to prepare planted concrete components.

[0003] 3D printing concrete technology has garnered widespread attention due to its advantages such as speed, convenience, and environmental friendliness. Unlike traditional mold-casting techniques, 3D printing concrete offers advantages such as high work efficiency, no need for formwork support, and environmental friendliness. Therefore, 3D printing can be used to produce concrete components for planting. This not only reduces mold investment but also greatly enhances the design freedom of components.

[0004] However, the workability requirements for concrete suitable for 3D printing are relatively high. Factors affecting printing performance include fluidity, extrudability, constructability, and crack resistance. In addition, the high porosity and low alkalinity requirements of planted concrete place high demands on 3D printed planted concrete materials. That is, 3D printed planted concrete materials need to meet the requirements of both planted concrete and 3D printed concrete. Summary of the Invention

[0005] The main objective of this invention is to provide a 3D-printed vegetation concrete material, mortar, component, and preparation method to solve the technical problem that 3D-printed concrete cannot simultaneously meet the requirements of both vegetation concrete and 3D-printed concrete.

[0006] To achieve the above objectives, the present invention provides a 3D-printed vegetation concrete material, comprising, by weight:

[0007] The composition comprises 100 parts of high-solid-waste low-alkali cementitious material, 60-70 parts of sand, 10-35 parts of spherical ceramic sand, 0.10-0.30 parts of retarder, 0.02-0.04 parts of hardening accelerator, 0.03-0.05 parts of water-retaining agent, 0.30-0.60 parts of thixotropic lubricant, and 35-45 parts of water. The raw materials for the high-solid-waste low-alkali cementitious material include slag, steel slag, sulfoaluminate cement clinker, fluorogypsum, and an activator. In the high-solid-waste low-alkali cementitious material, the total mass fraction of the slag, steel slag, and fluorogypsum is ≥75%.

[0008] High-solids, low-alkali cementitious materials meet the following performance indicators: specific surface area ≥ 450 m² 2 / kg, initial setting time ≥45min, final setting time ≤4h, 3d compressive strength ≥22MPa. 28d compressive strength ≥42.5MPa, pH value ≤8.00.

[0009] According to an embodiment of this application, the product comprises, by weight:

[0010] The mixture consists of 100 parts of high-solid-waste low-alkali cementitious material, 65-70 parts of sand, 15-23 parts of spherical ceramic sand, 0.25-0.30 parts of retarder, 0.03-0.04 parts of hardening accelerator, 0.03-0.04 parts of water-retaining agent, 0.30-0.50 parts of thixotropic lubricant, and 35-40 parts of water.

[0011] According to the embodiments of this application, the high solid waste low alkali cementitious material comprises, by weight, 55-60 parts of slag, 15-20 parts of steel slag, 15-20 parts of sulfoaluminate cement clinker, 8-12 parts of fluorogypsum, and 2-3 parts of activator.

[0012] According to the embodiments of this application, the particle size of the sand ranges from 0.60 mm to 1.18 mm. The spherical ceramic sand has a sphericity ≥ 0.75, a density grade of 800, and a particle size range of 0.60 mm to 2.36 mm.

[0013] According to embodiments of this application, the retarder is at least one selected from boric acid, sodium citrate, and sodium hexametaphosphate. The hardening accelerator is at least one selected from lithium carbonate, lithium sulfate, and lithium chloride. The water-retaining agent is hydroxypropyl methylcellulose ether with a viscosity of 4000 mPa·s to 10000 mPa·s. The thixotropic lubricant is magnesium aluminum silicate or attapulgite.

[0014] According to the embodiments of this application, the slag has an alkalinity coefficient ≥1.2 and a moisture content ≤2%, and is water-quenched granular slag. The steel slag has an alkalinity ≥2 and a moisture content ≤2%, and is hot-quenched steel slag. The fluorogypsum has a CaSO4 content ≥85%.

[0015] According to the embodiments of this application, the activator, by weight, includes 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate.

[0016] This application also provides a method for preparing the above-mentioned 3D printed vegetation concrete material, including the following steps:

[0017] After wetting the spherical ceramic sand, mix it evenly with high solid waste low alkali cementitious materials, sand particles, spherical ceramic sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, and water.

[0018] According to an embodiment of this application, the step of wetting the spherical ceramic sand includes immersing the spherical ceramic sand in water for at least 1 hour.

[0019] This application also provides a mortar for 3D printing vegetation concrete material, comprising, by weight:

[0020] The composition comprises 100 parts of high-solid-waste low-alkali cementitious material, 60-70 parts of sand, 10-35 parts of spherical ceramic sand, 0.10-0.30 parts of retarder, 0.02-0.04 parts of hardening accelerator, 0.03-0.05 parts of water-retaining agent, and 0.30-0.60 parts of thixotropic lubricant. The raw materials for the high-solid-waste low-alkali cementitious material include slag, steel slag, sulfoaluminate cement clinker, fluorogypsum, and an activator. In the high-solid-waste low-alkali cementitious material, the total mass fraction of the slag, steel slag, and fluorogypsum is ≥75%.

[0021] High-solids, low-alkali cementitious materials meet the following performance indicators: specific surface area ≥ 450 m² 2 / kg, initial setting time ≥45min, final setting time ≤4h, 3d compressive strength ≥22MPa. 28d compressive strength ≥42.5MPa, pH value ≤8.00.

[0022] This application also provides a 3D printed vegetation concrete component, which is formed by printing with the above-mentioned 3D printed vegetation concrete material or by printing with mortar of the above-mentioned 3D printed vegetation concrete material mixed with water.

[0023] The aforementioned 3D-printed vegetated concrete material uses high-solid-waste, low-alkali cementitious materials instead of ordinary silicate cement, and employs low-pH sulfur-aluminate cement clinker and fluorogypsum, which effectively reduces the alkalinity of the system while ensuring the strength of the concrete components. Furthermore, the use of ceramsite and sand aggregates to form the concrete aggregate increases the system's porosity. After the printed components are put into use, the original pores can absorb water or nutrient solution to supply the plants. This 3D-printed vegetated concrete material combines fluidity, extrudability, constructability, crack resistance, high porosity, and low alkalinity, meeting the requirements of both vegetated concrete and 3D-printed concrete. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0026] This invention provides a 3D-printed vegetation concrete material, comprising, by weight:

[0027] The composition comprises 100 parts of high-solid-waste low-alkali cementitious material, 60-70 parts of sand, 10-35 parts of spherical ceramic sand, 0.10-0.30 parts of retarder, 0.02-0.04 parts of hardening accelerator, 0.03-0.05 parts of water-retaining agent, 0.30-0.60 parts of thixotropic lubricant, and 35-45 parts of water. The raw materials for the high-solid-waste low-alkali cementitious material include slag, steel slag, sulfoaluminate cement clinker, fluorogypsum, and an activator. In the high-solid-waste low-alkali cementitious material, the total mass fraction of the slag, steel slag, and fluorogypsum is ≥75%.

[0028] High-solids, low-alkali cementitious materials meet the following performance indicators: specific surface area ≥ 450 m² 2 / kg, initial setting time ≥45min, final setting time ≤4h, 3d compressive strength ≥22MPa. 28d compressive strength ≥42.5MPa, pH value ≤8.00.

[0029] First, it should be noted that the weight percentage mainly indicates the weight ratio of each ingredient in the formula, that is, it reflects the relative weight relationship between each ingredient.

[0030] High-solid-waste, low-alkali cementitious materials are characterized by high solid waste content and low alkalinity. These include slag, steel slag, sulfoaluminate cement clinker, fluorogypsum, and activators. Specifically, high solid waste content refers to the total mass fraction of the slag, steel slag, and fluorogypsum being ≥75%.

[0031] Slag is a molten material mainly composed of silicates and aluminosilicates, formed by the reaction of impurities in iron ore with lime and other substances during the blast furnace ironmaking process. After quenching, it becomes a loose and porous granular material.

[0032] Steel slag is a byproduct of the steelmaking process. It consists of various oxides formed by the oxidation of impurities such as silicon, manganese, phosphorus, and sulfur in pig iron during smelting, as well as salts formed by the reaction of these oxides with solvents. Steel slag contains many useful components, such as metallic iron, calcium oxide, magnesium oxide, and manganese oxide, and can be used as a raw material in iron and steel metallurgy.

[0033] Fluorogypsum's main component is anhydrous calcium sulfate type II, and it also contains small amounts of impurities such as calcium fluoride, hydrogen fluoride, and sulfuric acid.

[0034] An activator is a chemical additive used to accelerate the cement curing reaction and improve the strength and hardness of concrete.

[0035] Sulfoaluminate cement clinker is the main component of sulfoaluminate cement. Besides sulfoaluminate cement clinker, sulfoaluminate cement also contains limestone powder and anhydrite. Due to its higher purity, sulfoaluminate cement clinker has higher reactivity and better activation effect. Under the same conditions, sulfoaluminate cement may require a larger admixture to achieve similar results, resulting in lower cost-effectiveness.

[0036] In some embodiments, the moisture content of slag, steel slag, and fluorogypsum is ≤2%.

[0037] The above raw materials can be mixed to prepare a high-solid-waste, low-alkali cementitious material, which can then be combined with other raw materials to obtain a 3D-printed vegetated concrete material. The high-solid-waste, low-alkali cementitious material meets the following performance indicators: specific surface area ≥ 450 m² / g. 2 / kg, initial setting time ≥45min, final setting time ≤4h, 3d compressive strength ≥22MPa. 28d compressive strength ≥42.5MPa, pH value ≤8.00.

[0038] Sand is a fine grain of sand, mainly composed of mineral particles. Depending on its source, it can be divided into natural sand and manufactured sand. Manufactured sand is sand produced by mechanically crushing and screening larger rocks. For example, limestone or basalt is crushed and screened to obtain manufactured sand.

[0039] Spherical ceramic sand consists of ceramic sand particles that are generally spherical in shape and relatively small. The internal structure of ceramic sand is characterized by a dense honeycomb-like micropore structure. These micropores are closed, not interconnected. This structure is formed by gas being trapped within the shell, which is the main reason for the high porosity and low density of ceramic sand.

[0040] There are various raw materials for preparing ceramic sand, such as clay and fly ash. Ceramic sand can be produced through processes such as processing, granulation, and calcination. Spherical ceramic sand can be made from fly ash, coal gangue, river mud, etc.

[0041] Compared to other shapes of ceramic sand, spherical ceramic sand can improve the fluidity of freshly mixed mortar and enhance its pumpability without clogging the pump.

[0042] Retarders are additives that delay the hydration reaction of cement or gypsum, thereby extending the setting time of concrete. There are many types of retarders, commonly used ones include lignin sulfonates and their derivatives, low molecular weight cellulose and their derivatives, hydroxycarboxylic acids (salts), organophosphonic acids (salts), boric acids (salts), and complexes.

[0043] Hardening accelerators can improve the early strength and early hardness of concrete. Specifically, they accelerate the rate and extent of cement hydration in concrete, thereby increasing early strength and hardness and allowing the concrete to reach its service requirements more quickly. Furthermore, by speeding up the cement hydration reaction, hardening accelerators can shorten the curing period, expedite project completion, and improve construction efficiency.

[0044] Water-retaining agents give 3D-printed vegetation concrete materials excellent water retention and thickening effects, significantly improving their workability. Specifically, water-retaining agents can extend the workability of 3D-printed vegetation concrete materials, such as ensuring they meet requirements of more than 60 minutes. Water-retaining agents can be cellulose ethers, such as one or more of methylcellulose ether, carboxymethylcellulose ether, hydroxypropyl methylcellulose ether, starch ether, or carboxyethylcellulose ether.

[0045] Thixotropic lubricants are special additives primarily used to improve the workability and anti-sagging properties of powdered or paste-like materials. They are typically composed of inorganic thixotropic agents and organic bentonite, and possess high suspending, thickening, thixotropic, and chemical stability.

[0046] The 35-45 parts water in the aforementioned 3D-printed vegetation concrete material are mixing water, used to mix all the raw materials evenly. In other words, the 3D-printed vegetation concrete material is a wet mortar.

[0047] Overall, high-solid-waste, low-alkali cementitious materials are the binder, the source of system strength, and a major factor affecting pH. They also influence the overall porosity of concrete; excessive cementitious material content will reduce porosity. Sand and spherical ceramsite are both aggregates, with sand filling the pores of ceramsite. Too much spherical ceramsite results in low strength in the 3D-printed vegetation concrete, while too little results in insufficient porosity.

[0048] The aforementioned 3D-printed vegetated concrete material uses high-solid-waste, low-alkali cementitious materials instead of ordinary silicate cement, and employs low-pH sulfur-aluminate cement clinker and fluorogypsum, which effectively reduces the alkalinity of the system while ensuring the strength of the concrete components. Furthermore, the use of ceramsite and sand aggregates to form the concrete aggregate increases the system's porosity. After the printed components are put into use, the original pores can absorb water or nutrient solution to supply the plants. This 3D-printed vegetated concrete material combines fluidity, extrudability, constructability, crack resistance, high porosity, and low alkalinity, meeting the requirements of both vegetated concrete and 3D-printed concrete.

[0049] In some embodiments, the components, by weight, include:

[0050] The mixture consists of 100 parts of high-solid-waste low-alkali cementitious material, 65-70 parts of sand, 15-23 parts of spherical ceramic sand, 0.25-0.30 parts of retarder, 0.03-0.04 parts of hardening accelerator, 0.03-0.04 parts of water-retaining agent, 0.30-0.50 parts of thixotropic lubricant, and 35-40 parts of water.

[0051] Under this formulation, the fluidity, extrusion, constructability, crack resistance, high porosity, and low alkalinity of the aforementioned 3D-printed vegetation concrete material are further improved, making it more suitable for the needs of vegetation concrete and 3D-printed concrete.

[0052] In some embodiments, the high-solid-waste, low-alkali cementitious material comprises, by weight, 55-60 parts of slag, 15-20 parts of steel slag, 15-20 parts of sulfoaluminate cement clinker, 8-12 parts of fluorogypsum, and 2-3 parts of activator.

[0053] The mass fractions here refer only to the relative weight relationships of the raw materials in the high-solid-waste, low-alkali cementitious material. One part by weight in the high-solid-waste, low-alkali cementitious material is not necessarily the same as one part by weight in the overall 3D-printed vegetation concrete material.

[0054] The preparation process of the high solid waste low alkali cementitious material is as follows: the moisture content of the raw materials slag, steel slag and fluorogypsum is detected and controlled to be ≤2%. If the moisture content exceeds the standard, it needs to be dried to meet the moisture content requirements. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters the ball mill for grinding. The qualified particles are selected away by the classifier, and the particles that do not meet the fineness requirements (i.e., the specific surface area is not qualified) are sent back to the mill for further grinding until the fineness of the product is qualified. The qualified cementitious material powder is sent into the finished product warehouse.

[0055] In some embodiments, the particle size of the sand ranges from 0.60 mm to 1.18 mm. The spherical ceramic sand has a sphericity ≥ 0.75, a density grade of 800, and a particle size range of 0.60 mm to 2.36 mm.

[0056] The more concentrated the particle size of sand and spherical ceramic sand, the greater the porosity of the concrete constructed by the 3D printed vegetation concrete material, making it easier to meet the needs of plant growth in vegetation concrete.

[0057] However, the porosity of concrete is not always better the higher it is; otherwise, the concrete strength will be too low and it will not meet the requirements for normal use. In order to balance porosity and strength, the aggregate approach adopted in this invention is to partially fill (not completely fill) the pores formed by spherical ceramic sand with finer sand particles. At the same time, the 3D printed vegetation concrete material is mixed with water to form a wet mixture. The wet mixture is required to have fluidity, pumpability, thixotropy, and support, all of which are affected by the type, particle size and composition of aggregates. If the particle size of sand and spherical ceramic sand is too large, it will reduce the fluidity and pumpability of the wet mixture.

[0058] After comprehensive consideration and extensive experimentation, sand particles within the aforementioned particle size range, as well as spherical ceramsite sand with specific sphericity, density grade, and particle size range, were determined. 3D-printed vegetation concrete materials using sand particles and spherical ceramsite meeting these conditions exhibit good wet-mix flowability, pumpability, thixotropy, and support properties, and demonstrate balanced porosity and concrete strength.

[0059] In some embodiments, the retarder is at least one of boric acid, sodium citrate, and sodium hexametaphosphate. The hardening accelerator is at least one of lithium carbonate, lithium sulfate, and lithium chloride. The water-retaining agent is hydroxypropyl methylcellulose ether with a viscosity of 4000 mPa·s to 10000 mPa·s. The thixotropic lubricant is any one of magnesium aluminum silicate or attapulgite.

[0060] In some embodiments, the retarder includes boric acid, sodium citrate, and sodium hexametaphosphate. To reduce the difficulty of formulating the retarder, in other embodiments, the retarder is one or any combination of two of boric acid, sodium citrate, and sodium hexametaphosphate. Similarly, lithium carbonate, lithium sulfate, and lithium chloride all have the effect of accelerating hardening and increasing early strength, and their mechanisms are similar. The hardening accelerator can be one of lithium carbonate, lithium sulfate, and lithium chloride, any combination of two, or a combination of three. To reduce the difficulty of formulation, the hardening accelerator is one of lithium carbonate, lithium sulfate, and lithium chloride.

[0061] In some embodiments, the slag has an alkalinity coefficient ≥1.2 and a moisture content ≤2%, and is water-quenched granular slag. The steel slag has an alkalinity ≥2 and a moisture content ≤2%, and is hot-quenched steel slag. The fluorogypsum has a CaSO4 content ≥85%.

[0062] In some embodiments, the activator comprises, by weight, 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate.

[0063] The preparation process of the activator is as follows: sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine and aluminum sulfate are measured in proportion and then put into a forced mixer to mix evenly to obtain a semi-finished activator. Then, fly ash and the semi-finished activator are measured separately according to the formula ratio and put into a mixer to dry mix evenly.

[0064] The 3D-printed vegetation concrete materials in the above embodiments meet the following conditions: pH value ≤ 7.5, fluidity 170mm~190mm, setting time ≥ 60min and ≤ 90min, workable time ≥ 30min, 12h compressive strength ≥ 6MPa, 28d compressive strength ≥ 20MPa, concrete drying shrinkage ≤ 0.04%, and porosity ≥ 25%.

[0065] This application also provides a method for preparing the above-mentioned 3D printed vegetation concrete material, including the following steps:

[0066] After wetting the spherical ceramic sand, mix it evenly with high solid waste low alkali cementitious materials, sand particles, spherical ceramic sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, and water.

[0067] Specifically, the activator and high-solid-waste low-alkali cementitious material can be prepared first and then weighed according to the formula ratio. The high-solid-waste low-alkali cementitious material, sand, spherical ceramic sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, water, etc. are then prepared. The spherical ceramic sand is then moistened. All raw materials are then stirred evenly. If they are put into a vertical shaft planetary mixer and stirred for no less than 3 minutes, 3D printed vegetation concrete material can be prepared.

[0068] In some embodiments, the step of wetting the spherical ceramic sand includes immersing the spherical ceramic sand in water for at least 1 hour.

[0069] The soaking water in this step is not the pre-measured mixing water; soaking allows the clay sand to become wet and absorbent.

[0070] This application also provides a mortar for 3D printing vegetation concrete material, comprising, by weight:

[0071] The composition comprises 100 parts of high-solid-waste low-alkali cementitious material, 60-70 parts of sand, 10-35 parts of spherical ceramic sand, 0.10-0.30 parts of retarder, 0.02-0.04 parts of hardening accelerator, 0.03-0.05 parts of water-retaining agent, and 0.30-0.60 parts of thixotropic lubricant. The raw materials for the high-solid-waste low-alkali cementitious material include slag, steel slag, sulfoaluminate cement clinker, fluorogypsum, and an activator. In the high-solid-waste low-alkali cementitious material, the total mass fraction of the slag, steel slag, and fluorogypsum is ≥75%.

[0072] High-solids, low-alkali cementitious materials meet the following performance indicators: specific surface area ≥ 450 m² 2 / kg, initial setting time ≥45min, final setting time ≤4h, 3d compressive strength ≥22MPa. 28d compressive strength ≥42.5MPa, pH value ≤8.00.

[0073] The mortar used in the aforementioned 3D-printed vegetation concrete material is a dry mortar, which differs from traditional 3D-printed vegetation concrete materials in that it does not contain water. It can be prepared by adding an appropriate amount of water to create a wet mortar, thus obtaining the aforementioned 3D-printed vegetation concrete material. The dry mortar form of this 3D-printed vegetation concrete material facilitates transportation and preparation. Furthermore, it possesses the same technical effects as traditional 3D-printed vegetation concrete materials.

[0074] This application also provides a 3D printed vegetation concrete component, which is formed by printing with the above-mentioned 3D printed vegetation concrete material or by printing with mortar of the above-mentioned 3D printed vegetation concrete material mixed with water.

[0075] The technical solution of this application will be described below with reference to specific embodiments.

[0076] In the following examples, unless otherwise specified, all raw materials used are commercially available products.

[0077] Sulfoaluminate cement clinker: Sulfoaluminate cement clinker powder, Anda brand, with a particle size range of 4-10mm, purchased from Hubei Yicheng Anda Special Cement Co., Ltd.

[0078] Fluorogypsum: Calcium sulfate content is 90wt%, specific surface area is 300m². 2 / kg, purchased from Hunan Nonferrous Chenzhou Fluorochemical Co., Ltd.;

[0079] Slag: Particle size range of 2-6mm, purchased from Wuhan Wuxin New Building Materials Co., Ltd.;

[0080] Steel slag: particle size range of 3-8mm, purchased from Wuhan Wuxin New Building Materials Co., Ltd.;

[0081] Manufactured sand: Manufactured sand with a particle size range of 0.60mm to 1.18mm, purchased from Huaxin New Building Materials Co., Ltd.

[0082] Spherical ceramic sand: Spherical ceramic sand with a particle size range of 0.60mm to 2.36mm, purchased from Anhui Zhaode Environmental Protection Technology Co., Ltd.

[0083] Ordinary Portland cement P·O42.5: purchased from Huaxin Cement Co., Ltd. Yangxin Plant.

[0084] Fly ash: Class II fly ash, purchased from Wuhan Qingshan Power Plant.

[0085] Sodium lignosulfonate: purchased from Zibo Yueyang Chemical Technology Co., Ltd.

[0086] Sodium sulfate: purchased from Jiangsu Fuzhan Pharmaceutical Co., Ltd.

[0087] Ferrous sulfate: purchased from Suqian Meineng Biotechnology Co., Ltd.

[0088] Triethanolamine: Purchased from Shandong Rongsheng New Materials Co., Ltd.

[0089] Aluminum sulfate: purchased from Shandong Zhongrun Haihua Chemical Technology Co., Ltd.

[0090] Sodium citrate: purchased from Nanjing Stebo Trading Co., Ltd.

[0091] Boric acid: purchased from Shanghai Yingshan New Materials Technology Co., Ltd.

[0092] Sodium citrate: purchased from Shanghai Yingshan New Materials Technology Co., Ltd.

[0093] Sodium hexametaphosphate: purchased from Weifang Pengchuang Chemical Co., Ltd.

[0094] Attapulgite clay: purchased from Shanghai Shangnan New Materials Co., Ltd.

[0095] Magnesium aluminum silicate: purchased from Hunan Pengtai High-Tech Materials Co., Ltd.

[0096] Lithium carbonate: purchased from Guangdong Longhu Technology Co., Ltd.

[0097] Lithium sulfate: purchased from Guangdong Longhu Technology Co., Ltd.

[0098] Lithium chloride: purchased from Guangdong Longhu Technology Co., Ltd.

[0099] Hydroxypropyl methylcellulose ether: purchased from Shandong Heda Group Co., Ltd.

[0100] Example 1

[0101] This embodiment provides a 3D-printed vegetation concrete material based on high-solid-waste low-alkali cementitious material. The vegetation concrete is composed of 100 parts of high-solid-waste low-alkali cementitious material, 60 parts of manufactured sand, 30 parts of spherical ceramic sand, 0.20 parts of retarder (sodium citrate), 0.02 parts of hardening accelerator (lithium carbonate), 0.04 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 6000 mPa·s), 0.4 parts of thixotropic lubricant (attapulgite), and 40 parts of water.

[0102] The high-solid-waste, low-alkali cementitious material is composed of the following raw materials in parts by weight: 60 parts slag, 15 parts steel slag, 15 parts sulfoaluminate cement clinker, 10 parts fluorogypsum, and 2 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The preparation process of the activator involves metering sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to a specified ratio, mixing them in a forced mixer to obtain a semi-finished activator product, and then metering fly ash and the semi-finished activator product separately according to the formula ratio and mixing them evenly in a mixer.

[0103] The preparation process of the high-solid-waste low-alkali cementitious material is as follows: The moisture content of the raw materials, slag, steel slag, and fluorogypsum, is detected and controlled to be ≤2%. If the moisture content exceeds the standard, they must be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. Qualified particles are removed by a classifier, while particles that do not meet the fineness requirement are returned to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is then sent to the finished product silo. The performance indicators of the high-solid-waste low-alkali cementitious material are: specific surface area 480 m² / g. 2 / kg, initial setting time 90min, final setting time 3h, 3d compressive strength 23.6MPa; 28d compressive strength 45.6MPa, pH value 7.7.

[0104] In this embodiment, the preparation method of 3D printed vegetation concrete material based on high solid waste and low alkali cementitious material is as follows: First, prepare the activator: sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate are measured in proportion and then put into a forced mixer to mix evenly to obtain the activator semi-finished product. Then, fly ash and the activator semi-finished product are measured separately according to the formula and put into a mixer for dry mixing evenly. Next, prepare the high solid waste and low alkali cementitious material: detect and control the moisture content of raw materials slag, steel slag, and fluorogypsum to ≤2%. If the moisture content exceeds the standard, it needs to be dried to meet the moisture content requirement. Then, each raw material is measured by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. The qualified particles are removed by a classifier, and the unqualified particles are sent back to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is sent to the finished product silo. Next, weigh out the high solid waste low alkali cementitious material, manufactured sand, spherical ceramic sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, water, etc. according to the formula ratio and set aside; then soak the spherical ceramic sand in water (not the measured mixing water) for at least 1 hour to make the ceramic sand in a water-absorbing and moistened state; then put all the raw materials into a vertical shaft planetary mixer and stir for no less than 3 minutes to prepare 3D printed vegetation concrete material.

[0105] Example 2

[0106] This embodiment provides a 3D-printed vegetation concrete material based on high-solid-waste low-alkali cementitious material. The vegetation concrete is composed of 100 parts of high-solid-waste low-alkali cementitious material, 70 parts of manufactured sand, 25 parts of spherical ceramic sand, 0.30 parts of retarder (boric acid), 0.04 parts of hardening accelerator (lithium sulfate), 0.05 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 6000 mPa·s), 0.6 parts of thixotropic lubricant (magnesium aluminum silicate), and 38 parts of water.

[0107] The high-solid-waste, low-alkali cementitious material is composed of the following raw materials in parts by weight: 55 parts slag, 15 parts steel slag, 20 parts sulfoaluminate cement clinker, 10 parts fluorogypsum, and 2.5 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The preparation process of the activator involves metering sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to a specified ratio, mixing them in a forced mixer to obtain a semi-finished activator product, and then metering fly ash and the semi-finished activator product separately according to the formula ratio and mixing them evenly in a mixer.

[0108] The preparation process of the high-solid-waste low-alkali cementitious material is as follows: The moisture content of the raw materials, slag, steel slag, and fluorogypsum, is detected and controlled to be ≤2%. If the moisture content exceeds the standard, they must be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. Qualified particles are removed by a classifier, while particles that do not meet the fineness requirement are returned to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is then sent to the finished product silo. The performance indicators of the high-solid-waste low-alkali cementitious material are: specific surface area 490 m² / g. 2 / kg, initial setting time 85min, final setting time 3.5h, 3d compressive strength 22.7MPa; 28d compressive strength 45.3MPa, pH value 7.60.

[0109] The preparation method of the 3D printed vegetation concrete material based on high solid waste and low alkali cementitious material in this embodiment is the same as the preparation method in Example 1.

[0110] Example 3

[0111] This embodiment provides a 3D-printed vegetation concrete material based on high-solid-waste low-alkali cementitious material. The vegetation concrete consists of 100 parts of high-solid-waste low-alkali cementitious material, 65 parts of manufactured sand, 23 parts of spherical ceramic sand, 0.30 parts of retarder (sodium hexametaphosphate), 0.04 parts of hardening accelerator (lithium carbonate), 0.03 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 10000 mPa·s), 0.45 parts of thixotropic lubricant (magnesium aluminum silicate), and 37 parts of water.

[0112] The high-solid-waste, low-alkali cementitious material is composed of the following raw materials in parts by weight: 55 parts slag, 20 parts steel slag, 15 parts sulfoaluminate cement clinker, 10 parts fluorogypsum, and 3 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The preparation process of the activator involves metering sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to a specified ratio, mixing them in a forced mixer to obtain a semi-finished activator product, and then metering fly ash and the semi-finished activator product separately according to the formula ratio and mixing them evenly in a mixer.

[0113] The preparation process of the high-solid-waste low-alkali cementitious material is as follows: The moisture content of the raw materials, slag, steel slag, and fluorogypsum, is detected and controlled to be ≤2%. If the moisture content exceeds the standard, they must be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. Qualified particles are removed by a classifier, while particles that do not meet the fineness requirement are returned to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is then sent to the finished product silo. The performance indicators of the high-solid-waste low-alkali cementitious material are: specific surface area 500 m² / g.2 / kg, initial setting time 85min, final setting time 3.5h, 3d compressive strength 22.8MPa; 28d compressive strength 46.2MPa, pH value 7.50.

[0114] The preparation method of the 3D printed vegetation concrete material based on high solid waste and low alkali cementitious material in this embodiment is the same as the preparation method in Example 1.

[0115] Example 4

[0116] This embodiment provides a 3D-printed vegetation concrete material based on high-solid-waste low-alkali cementitious material. The vegetation concrete is composed of 100 parts of high-solid-waste low-alkali cementitious material, 70 parts of manufactured sand, 15 parts of spherical ceramic sand, 0.25 parts of retarder (boric acid), 0.03 parts of hardening accelerator (lithium carbonate), 0.04 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 10000 mPa·s), 0.50 parts of thixotropic lubricant (magnesium aluminum silicate), and 36 parts of water.

[0117] The high-solid-waste, low-alkali cementitious material is composed of the following raw materials in parts by weight: 60 parts slag, 20 parts steel slag, 12 parts sulfoaluminate cement clinker, 8 parts fluorogypsum, and 3 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The preparation process of the activator involves metering sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to a specified ratio, mixing them in a forced mixer to obtain a semi-finished activator product, and then separately metering the fly ash and the semi-finished activator product according to the formula ratio and dry-mixing them evenly in a mixer.

[0118] The preparation process of the high-solid-waste low-alkali cementitious material is as follows: The moisture content of the raw materials, slag, steel slag, and fluorogypsum, is detected and controlled to be ≤2%. If the moisture content exceeds the standard, they must be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. Qualified particles are removed by a classifier, while particles that do not meet the fineness requirement are returned to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is then sent to the finished product silo. The performance indicators of the high-solid-waste low-alkali cementitious material are: specific surface area 470 m² / g. 2 / kg, initial setting time 100min, final setting time 4h, 3d compressive strength 22.2MPa; 28d compressive strength 45.3MPa, pH value 7.20.

[0119] The preparation method of the 3D printed vegetation concrete material based on high solid waste and low alkali cementitious material in this embodiment is the same as the preparation method in Example 1.

[0120] Comparative Example 1

[0121] This comparative example provides a 3D-printed vegetation concrete material, which is composed of 100 parts of ordinary silicate cement P·O42.5, 60 parts of manufactured sand, 30 parts of spherical ceramic sand, 0.20 parts of retarder (sodium citrate), 0.02 parts of hardening accelerator (lithium carbonate), 0.04 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 6000 mPa·s), 0.4 parts of thixotropic lubricant (attapulgite), and 40 parts of water.

[0122] The preparation method of the 3D printed vegetation concrete material in this comparative example is as follows: P·O42.5 cement, manufactured sand, spherical ceramic sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, water, etc. are weighed according to the formula ratio and set aside; then the spherical ceramic sand is soaked in water (not the measured mixing water) for at least 1 hour to make the ceramic sand in a water-absorbing and moistened state; then all raw materials are put into a vertical shaft planetary mixer and stirred for no less than 3 minutes to prepare the 3D printed vegetation concrete material.

[0123] Comparative Example 2

[0124] This comparative example provides a 3D printed vegetation concrete material, which is composed of 100 parts of high solid waste low alkali cementitious material, 100 parts of manufactured sand, 0.20 parts of retarder (sodium citrate), 0.02 parts of hardening accelerator (lithium carbonate), 0.04 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 6000 mPa·s), 0.4 parts of thixotropic lubricant (attapulgite), and 40 parts of water.

[0125] The high-solid-waste, low-alkali cementitious material is composed of the following raw materials in parts by weight: 60 parts slag, 15 parts steel slag, 15 parts sulfoaluminate cement clinker, 10 parts fluorogypsum, and 2 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The activator is prepared by measuring sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to the specified proportions, mixing them in a forced mixer to obtain a semi-finished activator. Then, fly ash and the semi-finished activator are separately measured according to the formula and dry-mixed in a mixer until homogeneous.

[0126] The preparation process of high-solid-waste low-alkali cementitious material is as follows: The moisture content of raw materials slag, steel slag, and fluorogypsum is detected and controlled to be ≤2%. If the moisture content exceeds the standard, it needs to be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. Qualified particles are removed by a classifier, while particles that do not meet the fineness requirement are returned to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is then sent to the finished product silo. The performance indicators of the high-solid-waste low-alkali cementitious material are: specific surface area 480 m² / g. 2 / kg, initial setting time 90min, final setting time 3h, 3d compressive strength 23.6MPa; 28d compressive strength 45.6MPa, pH value 7.7.

[0127] In this embodiment, the preparation method of 3D printed vegetation concrete material based on high solid waste and low alkali cementitious material is as follows: First, prepare the activator: sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate are measured in proportion and then put into a forced mixer to mix evenly to obtain the activator semi-finished product. Then, fly ash and the activator semi-finished product are measured separately according to the formula and put into a mixer for dry mixing evenly. Next, prepare the high solid waste and low alkali cementitious material: detect and control the moisture content of raw materials slag, steel slag, and fluorogypsum to ≤2%. If the moisture content exceeds the standard, it needs to be dried to meet the moisture content requirement. Then, each raw material is measured by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. The qualified particles are removed by a classifier, and the unqualified particles are sent back to the mill for further grinding until the product fineness is qualified. The qualified cementitious material powder is sent to the finished product silo. Next, weigh out the high solid waste low alkali cementitious material, manufactured sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, water, etc. according to the formula ratio and set them aside; then put each raw material into a vertical shaft planetary mixer and mix for no less than 3 minutes to prepare 3D printed vegetation concrete material.

[0128] Comparative Example 3

[0129] This comparative example provides a 3D-printed vegetation concrete material, which is composed of 100 parts of high-solids-waste low-alkali cementitious material, 55 parts of manufactured sand, 40 parts of spherical ceramic sand, 0.10 parts of retarder (sodium hexametaphosphate), 0.03 parts of hardening accelerator (lithium carbonate), 0.03 parts of water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 6000 mPa·s), 0.3 parts of thixotropic lubricant (attapulgite), and 35 parts of water.

[0130] The high-solid-waste, low-alkali cementitious material is composed of the following raw materials in parts by weight: 55 parts slag, 15 parts steel slag, 20 parts sulfoaluminate cement clinker, 10 parts fluorogypsum, and 2.5 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The preparation process of the activator involves metering sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to a specified ratio, mixing them in a forced mixer to obtain a semi-finished activator product, and then metering fly ash and the semi-finished activator product separately according to the formula ratio and mixing them evenly in a mixer.

[0131] The preparation process of the high-solids-waste low-alkali cementitious material is as follows: The moisture content of the raw materials slag, steel slag, and fluorogypsum is detected and controlled to be ≤2%. If the moisture content exceeds the standard, they must be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material enters a ball mill for grinding. Qualified particles are removed by a classifier, while particles that do not meet the fineness requirement are returned to the mill for further grinding until the product fineness is qualified (specific surface area ≥450m²). 2 / kg), the finely sized cementitious material powder is sent to the finished product silo; the performance indicators of the high-solid-waste low-alkali cementitious material are: specific surface area 490m² 2 / kg, initial setting time 85min, final setting time 3.5h, 3d compressive strength 22.7MPa; 28d compressive strength 45.3MPa, pH value 7.60.

[0132] The preparation method of the 3D printed vegetation concrete material based on high solid waste and low alkali cementitious material in this comparative example is the same as the preparation method in Example 1.

[0133] Comparative Example 4

[0134] This embodiment provides a 3D-printed vegetation concrete material based on solid waste cementitious material. The vegetation concrete is composed of 100 parts solid waste cementitious material, 70 parts manufactured sand, 15 parts spherical ceramic sand, 0.25 parts retarder (boric acid), 0.03 parts hardening accelerator (lithium carbonate), 0.04 parts water-retaining agent (hydroxypropyl methylcellulose ether with a viscosity of 10000 mPa·s), 0.50 parts thixotropic lubricant (magnesium aluminum silicate), and 36 parts water.

[0135] The solid waste-based cementitious material is composed of the following raw materials in parts by weight: 50 parts slag, 10 parts steel slag, 21 parts sulfoaluminate cement clinker, 15 parts fluorogypsum, and 4 parts activator. The activator consists of 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate. The preparation process of the activator involves measuring sodium lignosulfonate, sodium sulfate, ferrous sulfate, triethanolamine, and aluminum sulfate according to a specified ratio, mixing them in a forced mixer to obtain a semi-finished activator product, and then separately measuring the fly ash and the semi-finished activator product according to the formula ratio and mixing them evenly in a mixer.

[0136] The preparation process of the solid waste-based cementitious material is as follows: The moisture content of the raw materials slag, steel slag, and fluorogypsum is detected and controlled to be ≤2%. If the moisture content exceeds the standard, they must be dried to meet the moisture content requirement. Then, each raw material is weighed by a weighing scale and batched according to the designed formula. Each material is then ground in a ball mill until it meets the grinding requirements (specific surface area ≥450 m²). 2 Particles weighing approximately 100 kg are separated by a classifier, while those that do not meet the fineness requirement are returned to the mill for further grinding until the final product meets the fineness requirement (specific surface area ≥ 450 m²).2 / kg), the finely sized cementitious material powder is sent to the finished product warehouse; the performance indicators of the solid waste-based cementitious material are: specific surface area 475m². 2 / kg, initial setting time 40min, final setting time 2.5h, 3d compressive strength 25.2MPa; 28d compressive strength 48.3MPa, pH value 9.20.

[0137] The preparation method of the 3D printed vegetation concrete material based on solid waste-based cementitious material in this comparative example is the same as the preparation method in Example 1.

[0138] The performance testing methods involved in the above examples are as follows:

[0139] 1) Determination of pH value of concrete: Take out the samples at 28 days of age, soak them in anhydrous ethanol solution for one week to stop hydration, dry them in a vacuum drying oven at 60℃ to constant weight, grind them in an agate mortar to below 0.08 mm, weigh 10 g of each sample, add 100 mL of distilled water, stir thoroughly, let stand for 2 h, and measure the pH value of the solution with a PH-2C digital acidity meter.

[0140] 2) Flowability test of 3D printed planted concrete material: The flowability of 3D printed planted concrete material was tested according to GB / T2419-2005 "Determination of Flowability of Cement Mortar".

[0141] 3) Operable time: Operable time is used to determine the time during which the concrete mixture can be continuously printed. The method is as follows: print the concrete mixture at intervals of 5 min to 10 min, and print strips with a length of not less than 100d (d is the diameter of the extruder head) by extrusion molding. Record the time corresponding to the interruption or discontinuity of the printed strip, which is recorded as the open time.

[0142] 4) Setting time, shrinkage rate, and compressive strength test: The setting time and shrinkage rate of the 3D printed vegetation concrete material were tested in accordance with JGJ / T 70-2009 "Standard for Test Methods of Basic Performance of Building Mortar"; the compressive strength of the printed mortar was tested in accordance with GB / T17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)".

[0143] 5) Porosity Test: (a) Print a 150mm×150mm×150mm permeable concrete specimen and cure it in a standard curing room until the desired age; (b) Dry the specimen in an oven at 105℃ until constant weight, then remove it and cool it to room temperature in a desiccator; (c) Place the measuring cylinder horizontally and pour water into it until the water level reaches the 0mm mark; (d) Place the permeable concrete specimen to be tested into the measuring cylinder. After the water level stabilizes and no air bubbles appear in the concrete block, directly read the scale value on the measuring cylinder. The formula for calculating porosity is as follows:

[0144]

[0145] In the formula, p represents the effective porosity (%).

[0146] s—Area of ​​the measuring cylinder (mm²) 2 );

[0147] A—Bottom area of ​​the test piece (mm²) 2 );

[0148] h—Height of the test piece (mm);

[0149] △—Increase in water level after the test specimen is placed in water and the water level stabilizes (mm).

[0150] The performance of the 3D-printed vegetation concrete materials obtained in each example was determined using the aforementioned testing methods. The specific results are shown in Table 1.

[0151] Table 1. Performance test results of 3D printed vegetated concrete materials obtained in each example.

[0152]

[0153] The results above show that the 3D-printed vegetation concrete material based on high-solid-waste low-alkali cementitious material provided by this invention has a pH value ≤ 7.5, a fluidity of 170 mm to 190 mm, a setting time ≥ 60 min and ≤ 90 min, a workable time ≥ 30 min, a 12-hour compressive strength ≥ 6 MPa, a 28-day compressive strength ≥ 20 MPa, a concrete drying shrinkage rate ≤ 0.04%, and a porosity ≥ 25%. It has good pumpability, extrudability, and constructability, and also possesses early strength, low shrinkage, and crack-free properties.

[0154] Comparative Example 1 uses ordinary Portland cement P·O42.5. The concrete material prepared by it has an excessively long setting time and insufficient 12-hour compressive strength and 28-day compressive strength, which do not meet the requirements.

[0155] Comparative Example 2 did not use ceramic sand, and the porosity of the concrete material prepared from it was too small, failing to meet the requirements.

[0156] The ratio of ceramic sand and manufactured sand in Comparative Example 3 was not appropriate, and the concrete material prepared by it had too low 28-day compressive strength and too high porosity, which did not meet the requirements.

[0157] The proportions of the high-solid-waste, low-alkali cementitious material in Comparative Example 4 were unsuitable, resulting in concrete with a high pH value and a short setting time, which did not meet the requirements for printing and use.

[0158] The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made using the contents of the present invention under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A 3D-printed vegetated concrete material, characterized in that, By weight, it includes: 100 parts of high-solid-waste low-alkali cementitious material, 65-70 parts of sand, 15-23 parts of spherical ceramic sand, 0.25-0.30 parts of retarder, 0.03-0.04 parts of hardening accelerator, 0.03-0.04 parts of water-retaining agent, 0.30-0.50 parts of thixotropic lubricant, and 35-40 parts of water; The raw materials of the high-solid-waste low-alkali cementitious material include slag, steel slag, sulfoaluminate cement clinker, fluorogypsum, and activator; in the high-solid-waste low-alkali cementitious material, the total mass fraction of the slag, steel slag, and fluorogypsum is ≥75%; By weight, the high-solid-waste low-alkali cementitious material includes 55-60 parts of slag, 15-20 parts of steel slag, 15-20 parts of sulfoaluminate cement clinker, 8-12 parts of fluorogypsum, and 2-3 parts of activator. The high-solids, low-alkali cementitious material meets the following performance requirements: specific surface area ≥ 450 m² 2 / kg, initial setting time ≥45min, final setting time ≤4h, 3d compressive strength ≥22MPa; 28d compressive strength ≥42.5MPa, pH value ≤8.00; The particle size of the sand is in the range of 0.60mm to 1.18mm; the spherical ceramic sand has a sphericity ≥0.75, a density grade of 800, and a particle size range of 0.60mm to 2.36mm. The activator comprises 25 parts fly ash, 0.5 parts sodium lignosulfonate, 50 parts sodium sulfate, 4.5 parts ferrous sulfate, 2 parts triethanolamine, and 18 parts aluminum sulfate.

2. The 3D-printed vegetated concrete material according to claim 1, characterized in that, The retarder is at least one of boric acid, sodium citrate, and sodium hexametaphosphate; the hardening agent is at least one of lithium carbonate, lithium sulfate, and lithium chloride; the water-retaining agent is hydroxypropyl methylcellulose ether with a viscosity of 4000 mPa·s to 10000 mPa·s; and the thixotropic lubricant is magnesium aluminum silicate or attapulgite.

3. The 3D-printed vegetated concrete material according to claim 1, characterized in that, The slag has an alkalinity coefficient ≥1.2 and a moisture content ≤2%, and the slag is water-quenched granular slag; the steel slag has an alkalinity ≥2 and a moisture content ≤2%, and the steel slag is hot-quenched steel slag; the fluorogypsum has a CaSO4 content ≥85%.

4. A method for preparing 3D-printed vegetation concrete material as described in any one of claims 1 to 3, characterized in that, Includes the following steps: After wetting the spherical ceramic sand, mix the high solid waste low alkali cementitious material, sand, spherical ceramic sand, retarder, hardening accelerator, water-retaining agent, thixotropic lubricant, and water evenly.

5. The preparation method according to claim 4, characterized in that, The step of wetting the spherical ceramic sand includes immersing the spherical ceramic sand in water for at least 1 hour.

6. A 3D-printed vegetation concrete component, characterized in that, Formed by printing the 3D-printed vegetation concrete material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Vegetation concrete and preparation method and application thereof

    CN110317008A

  • Low-alkali plant-growing concrete based on steel slag and preparation method of low-alkali plant-growing concrete

    CN115974511A